Determination of effective stress intensity factors under mixed‐mode from digital image correlation fields in presence of contact stresses and plasticity. (10th November 2019) - Bonniot, Thomas; Doquet, Véronique; Mai, Si Hai
Abstract: Digital image correlation (DIC) is more and more popular to monitor fatigue crack growth and to determine the stress intensity factors. However, the posttreatment of the recorded displacement fields becomes tricky when the crack faces are not stress‐free and when crack tip plasticity becomes significant. Several posttreatment methods to locate the crack tip and measure the effective stress intensity factors in such cases are compared, using finite element method‐computed displacement fields, and then used on real DIC fields. An approach coupling DIC and finite element method is proposed to estimate the contact stresses along the crack.